Construction of an Initial Assessment Documentation Tool for Nursing Recording System in Coronary Care Units - Shamoun, mona; Gourgees, Samira (Iraqi National Journal of Nursing Specialties, 2007)
Objective : The study was carried out to construct an initial assessment documentation tool for nursing recording system in Coronary Care Unit. Methodology : A descriptive, purposive sample of (65) nurses was selected from CCU of main teaching hospitals (Al Karama, Al Kindy, Al Kadimia, Al Yarmmok, Baghdad teaching hospital, Ibn Al Naffis hospital) and Ibn-Al betar hospital in Baghdad city from the 15th of April 2004 to the 15th of April 2006. The instrument was constructed and comprised of two sections: section one included the nurses’ demographic characteristic; section two was the initial assessment documentation tool that contained (2) parts including: General information form and the initial assessment form. Descriptive and inferential statistical procedures were used to analyze the data. Reliability of the instrument was determined for the tool parts and it was (0.85), besides that a panel of experts determined the validity of the tool. Results : The findings revealed that the most of the study sample were young male with nursing institute graduate and the majority of them employed with limited experience ranging between (1-5) years as general and experience in CCU. In spite of that no one of them got a training course in documenting their activities. The present study revealed that, the distribution of nurses’ responses to the health pattern indicated that the (health perception, exchanging, subjective awareness of information, nutrition-metabolic, elimination, activity and exercise, rest and sleep, cognitive-sensing, and relationship) patterns were the most appropriate, clear and comprehensive patterns for them. Most of the international nursing diagnosis items of the tool were clear for nurses except few items. The results also showed that there was a statistically significant influence between the nurses’ responses to the (11) health patterns with the age variable except in the cognitive - sensing pattern. Moreover, the level of education patterns significantly influences the entire sample responses.